Diagnosis and management of uveitis-glaucoma-hyphema syndrome - Guszkowska, Maria; Popowska, Monika; Lazicka-Galecka, Monika; Galecki, Tomasz; Kaminska, Anna; Szaflik, Jacek Pawel (Klinika Oczna / Acta Ophthalmologica Polonica, 2025)
We present a diagnostically challenging case of uveitis-glaucoma-hyphema (UGH) plus syndrome, emphasizing the importance of imaging modalities, particularly ultrasound biomicroscopy, in identifying intraocular lens (IOL)-related mechanical complications. A 42-year-old woman with a history of juvenile cataract surgery and posterior chamber IOL implantation presented with recurrent anterior uveitis, vitreous hemorrhage, and secondary glaucoma in the left eye. Despite multiple surgical interventions – including trabeculectomy, revision surgery, and pars plana vitrectomy – her symptoms persisted. Standard workup for infectious and autoimmune uveitis was negative. Ultrasound biomicroscopy revealed iris-IOL chafing, confirming the diagnosis of UGH plus syndrome. The malpositioned IOL was surgically explanted. This led to complete resolution of inflammation, cessation of hemorrhage, and long-term intraocular pressure (IOP) stabilization without the need for further surgical intervention. Uveitis-glaucoma-hyphema plus syndrome should be suspected in pseudophakic patients with recurrent anterior and vitreous hemorrhage unresponsive to conventional therapies. Early use of imaging and timely IOL explantation can prevent irreversible vision loss.